Discourseology of Linguistic Consciousness: Neural Network Modeling of some Structural and Semantic Relationships - Віталій Шимко (Психолінгвістика)
Objective. Study of the validity and reliability of the discourse approach for the psycholinguistic understanding of the nature, structure, and features of the linguistic consciousness functioning.